Top or Bottom? Varsity youth talk about gay sexuality in a Stepping Stones Workshop: Implications for sexual health - Kiguwa, P.; Nduna, M. (South African Journal of Higher Education, 2017)
This paper discusses the constructs of sexuality amongst a group of LGBTI university students during a Stepping Stones workshop aimed at exploring their engagement with sexual and reproductive health rights issues as it affects them. These constructs include notions of binary identities of being gay, such as being a ‘top’ versus being a ‘bottom’, that are then applied to sexual practices and behaviour that have serious implications for sexual health and bodily integrity. We discuss the intersections of gender identity, sexuality, sexual health and sexual rights, arguing that such constructs are not only limiting in their demarcations of sexual boundaries in relationships and for intimacy but also that attempts to engage sexual health promotion must take into account the intersecting identities of gender and sexuality that are tied to sexual behaviour.